STUDENTS’ COGNITIVE LANGUAGE LEARNING STRATEGY IN MASTERING ENGLISH MATERIAL AT VOCATIONAL SCHOOL LEVEL - Maemunah, Rizki; Susanto, Dias Andris (LPPM Institut Teknologi Dan Kesehatan Aspirasi, 2023)
In Indonesia, many students still cannot master English because they are not interested in learning English The appropriate learning strategy, which is suitable to the qualities and surroundings of the learners, is one of the factors in accomplishing English acquisition. This research aimed to know what cognitive strategy is most frequently used by the student at SMK N 4 Semarang and why them shoose that activity. This research applied a qualitative descriptive method. In collecting data, the researcher used an online survey through Gform and. SILL questions with a total number of fourteen questions related to the cognitive strategy was use to being the instrument. The subject of this research was X grade of mechanical engineering 4 at SMK N 4 Semarang which a total number of 36 male students. The data were analyzed by data reduction, data display, conclusion drawing, and verification. From the SILL questions, the findings showed that watching English language TV shows spoken in English or going to movies spoken in English was the most frequently used activity by the students with a percentage of 50%. And the least used strategy was to start a conversation in English with a percentage of 8,3%. These findings suggest the teachers apply that activity to improve the English skills of the student so that the students are interested in learning English.